Ambiguity on the use of ‘Kita’ personal pronoun among foreign students - Abdul Kadir, Fatin Rabiha; Hamzah, Zaitul Azma Zainon; Che Rodi, Rozita; Kamaruddin, Rohaidah (Human Resource Management Academic Research Society, 2022)
The aim of the study is to examine the ambiguity of The Malay Language Personal Pronoun (PP) among foreign students. The objective of this study is to identify and analyze ambiguity in the use of the reference ‘Kita’ Personal Pronoun among foreign students. This study is a field study and the data was obtained using observation methods and interviews. Next, this PP usage data is recorded using a recorder. A total of 24 sample people were selected as respondents to the study using non-probability sampling techniques. These respondents are students at the International Modern Arabic School, Putrajaya. The results of the study found that the blurring in the use of PP ‘kita’ among foreign speakers could be overcome with the sensitivity and authority of teachers in the interpreting weakness of foreign speakers. However, foreign speakers also need to be more focused and earnest in learning sessions to overcome this problem.